Climate change, its impact on crop production, challenges, and possible solutions - Majed ALOTAIBI (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2023)
Climate change poses serious threats to agriculture and food security, and extreme weather events have reduced crop productivity worldwide. Future projections predict that the average global temperature will rise by 2.0 to 6.4 °C and the increase in sea level will be 59 cm by the end of 21st century. The unprecedented rise in temperature has led to an increase in the incidence of heat waves, droughts, floods, and irregular patterns of precipitation. These changes have a dramatic impact on prevailing agricultural cropping systems, productivity, and food security of people regionally and globally. The change in climatic parameters have substantial effects on weeds, diseases, insect, and pests in different ways, and can result in an increase of their geographical distribution, number of generations, and survival during winter. Thus, to sustain the crop production on the eve of climate change is the main challenge. Therefore, adaptation measures are prerequisites to reduce the effects of climatic changes on production of agricultural crops. In this review, a brief insight has been given in the impact of climate change on agriculture and, the future challenges of climate change on the production of crops. In addition, integrated approaches, or recent developments for the improvement of crops such as breeding, transgenic approaches to biotechnology, and functional genomics, agronomic practices, cultivation of climate resilient crops, and nanotechnology for abiotic stress such as drought stress, temperature, heat, and salinity tolerance have also been discussed.